The Granulocyte-colony stimulating factor has a dual role in neuronal and vascular plasticity - Wallner, Stephanie; Peters, Sebastian; Pitzer, Claudia; Resch, Herbert; Bogdahn, Ulrich; Schneider, Armin (Frontiers in cell and developmental biology, 2015)
Granulocyte-colony stimulating factor (G-CSF) is a growth factor that has originally been identified several decades ago as a hematopoietic factor required mainly for the generation of neutrophilic granulocytes, and is in clinical use for that. More recently, it has been discovered that G-CSF also plays a role in the brain as a growth factor for neurons and neural stem cells, and as a factor involved in the plasticity of the vasculature. We review and discuss these dual properties in view of the neuroregenerative potential of this growth factor.
Gesehen am 26.06.2020